Viable but nonculturable Vibrio cholerae O1 in the aquatic environment of Argentina - Binsztein, Norma (2004)
Fil: Binsztein, Norma. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología; Argentina.